Case Report: High Prenatal Bisphenol A Exposure and Infant Neonatal Neurobehavior - Sathyanarayana, Sheela (National Institute of Environmental Health Sciences, 2011)
Context: Most of the U.S. population is exposed to the high-production-volume chemical bisphenol A (BPA), but targetable sources of exposure remain to be determined. Animal studies and one human study suggest that BPA is a neurotoxicant. Case presentation: A mother in the Health Outcomes and Measures of the Environment (HOME) Study, a prospective birth cohort examining prenatal and postnatal environmental toxicants and childhood health outcomes, had a urinary BPA concentration of 583 µg/g creatinine at 27 weeks of pregnancy, which was the highest concentration observed in this cohort (median, 2.0 µg/g creatinine) and the general population. We used prenatal questionnaire data and a follow-up interview to identify potential sources of exposure that included daily plastic use and consumption of canned beverages and foods. Her male infant had a normal newborn neurobehavioral assessment but presented with abnormalities at the 1-month examination that prompted physician referral. Subsequently, the child had normal neurobehavioral testing results at annual evaluations from 1 to 5 years of age. Discussion: Investigations into sources of high gestational urinary BPA concentrations provide an opportunity to identify potential targets for reduction of BPA exposure. This case highlights a potential link between gestational BPA exposure and transient neurobehavioral changes that is hypothesis generating and can serve to alert researchers to potential areas for examination in future studies. Relevance to clinical practice: It is important to educate health care practitioners regarding potential sources of BPA exposure and anticipatory guidance on minimization of exposures during vulnerable periods of development.